A flexural ductility model for UHPC beams reinforced with FRP bars. (November 2022) - Tan, Hongmei; Hou, Zhujian; Li, Yida; Xu, Xiaoqing
Abstract: Ultra-high performance concrete (UHPC) beams reinforced with fiber-reinforced polymer (FRP) bars (FRP-UHPC beams) exhibit high flexural stiffness and small crack width at the serviceability limit state. However, a proper model considering FRP-UHPC beams' mechanical characteristics is lacking to evaluate their flexural ductility. In this paper, based on a rigorous nonlinear cross-section analysis and the conjugate beam method, the applicability of existing ductility models of FRP bar-reinforced normal concrete beams (FRP-NC beams) to FRP-UHPC beams was discussed, and these ductility models were modified after investigating the FRP-UHPC beams' strain limits in serviceability limit state. A new model by setting the FRP's allowable strain in Newhook model as 3000με was finally adopted after considering that FRP-UHPC beams have smaller crack width. Calculation results by the modified Newhook model suggested that high reinforcement ratio in FRP-UHPC beams has unfavorable effect on the flexural ductility. Moreover, the influence of key material parameters, including the compressive strength of UHPC, peak compressive strain of UHPC, first cracking strength of UHPC and the type of FRP bars, on the flexural ductility was analyzed. Finally, a theoretical model for predicting overall factor-reinforcement ratio curve calculated by the modified Newhook model was proposed.